
12.5×5.5 62.5×0.9巧算
展开全部
12.5x5.5
=(12+0.5)(5+0.5)
=60+6+2.5+0.25
=68.75
62.5x0.9
=(60+2.5)(1-0.1)
=60-6+2.5-0.25
=62.5-6.25
=56.25
=(12+0.5)(5+0.5)
=60+6+2.5+0.25
=68.75
62.5x0.9
=(60+2.5)(1-0.1)
=60-6+2.5-0.25
=62.5-6.25
=56.25
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
12.5*5.5
=12.5*2*(5.5*2)/4
=25*11/4
=275/4
=68.75
62.5*0.9
=62.5*(1-0.1)
=62.5-6.25
=56.25
=12.5*2*(5.5*2)/4
=25*11/4
=275/4
=68.75
62.5*0.9
=62.5*(1-0.1)
=62.5-6.25
=56.25
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询